Benthic biotope index for classifying habitats in the sado estuary: Portugal - Caeiro, Sandra (2011)
An integration of sediment physical, chemical, biological, and toxicity data is necessary for a meaningful interpretation of the complex sediment conditions in the marine environment. Assessment of benthic community is a vital component for that interpretation, yet their evaluation is complex and requires a large expenditure of time and funds. Thus, there is a need for new tools that are less expensive and more understandable for managers. This paper presents a benthic biotope index to predict from physical and chemical variables the occurrence of macrobenthic habitats. Parameters such as sediment type, organic matter, depth, and hydrodynamic parameters were selected, through a discriminant analysis, to compute the index. Other authors have used multivariate methods to determine the benthic biotopes for Sado Estuary. The index proved to be a valid tool to classify and assess the spatial patterns of benthic habitat and to synthesize stress biotope gradients.